Does Accounting Information Systems (AIS) Important for MSMEs? Case Study on MSMEs in Yogyakarta Towards SDG 8 - Tatik Tatik; Doddy Setiawan; Falikhatun Falikhatun; Taufiq Arifin (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: The study aims to examine the implementation and development of Accounting Information Systems (AIS) in Micro, Small, and Medium Enterprises (MSMEs) in Yogyakarta and identify factors influencing AIS adoption to support sustainable economic growth aligned with Sustainable Development Goal (SDG) 8. Method: The research employed a qualitative approach using a multi-case study method involving three MSMEs representing micro, small, and medium business categories. Data were collected through in-depth interviews, observations, documentation, and literature studies. The data analysis followed an interactive model consisting of data reduction, data display, and conclusion verification. Results: The findings reveal differences in AIS implementation among MSMEs based on business scale and organizational resources. Micro businesses still rely on manual accounting systems due to limited financial resources, inadequate human resource competencies, and insufficient technological infrastructure. Small businesses have adopted digital AIS through external software providers, while medium businesses have developed integrated AIS using internal developers. AIS implementation provides benefits including improved financial information accuracy, operational efficiency, internal control, and strategic decision-making capabilities. Novelty: The study contributes empirical evidence regarding the different stages of AIS adoption among MSMEs and highlights the importance of aligning technological capability, financial readiness, and human resource development to achieve sustainable digital transformation. The findings support SDG 8 by strengthening MSME competitiveness and promoting inclusive economic growth through technology-based management systems.